Scenery - living matter (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
Scenography is located at the same time in a space of intersection involved with the living arts. We recovered the concept of Adolphe Appia, for a “Work of living art”, enunciating a temporal ellipse of exploration of an aspect of the implicated and relational art. To this condition of being “alive” in art, today we have to add a set of different meanings that are somehow related to our field of work: I speak of participation, implication, citizenship, interaction, stated in a need to have a voice, take sides and risk solutions. The exploration of the concepts of place, public space for interaction and intervention enunciates artistic actions in a context that is important to value and deepen.
Keywords: Scenography; Public space; Art in Context